2018
DOI: 10.1177/0193945918808766
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Cluster Science in Chronic Kidney Disease: A Literature Review

Abstract: The purpose of this review was to synthesize evidence on symptom clusters in patients with chronic kidney disease (CKD). The quality of studies was evaluated using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Twelve articles met inclusion criteria. Patients had CKD ranging from Stages 2 through 5. Most studies determined clusters using variable-centered approaches based on symptoms; however, one used a person-centered approach based on demographic and clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 52 publications
0
35
1
Order By: Relevance
“…Variable-centered approaches to clustering, which seek to identify relationships among symptoms and quantify the patient's symptom experience, have been employed in patients with ESRD (Amro et al, 2015;Yu, Huang, & Tsai, 2012). Fatigue (Jhamb et al, 2013;Rodrigue et al, 2011), sleep disturbance (Nigam, Camacho, Chang, & Riaz, 2018), depression/anxiety (Assari & Burgard, 2015), pain (Song, Paul, Ward, Gilet, & Hladik, 2018), and gastrointestinal symptoms (Zhang, Bansal, Go, & Hsu, 2015) are among the most common co-occurring symptoms in CKD (Lockwood et al, 2019). Although variable center approaches are useful in examining relationships among homogeneous populations (Conley, 2017), variable-centered approaches to clustering symptoms are complicated by difficulty interpreting symptom clusters due to heterogeneity of symptom response patterns, thereby limiting their clinical utility (Conley, 2017;Lockwood et al, 2019;Ryan et al, 2019).…”
mentioning
confidence: 99%
“…Variable-centered approaches to clustering, which seek to identify relationships among symptoms and quantify the patient's symptom experience, have been employed in patients with ESRD (Amro et al, 2015;Yu, Huang, & Tsai, 2012). Fatigue (Jhamb et al, 2013;Rodrigue et al, 2011), sleep disturbance (Nigam, Camacho, Chang, & Riaz, 2018), depression/anxiety (Assari & Burgard, 2015), pain (Song, Paul, Ward, Gilet, & Hladik, 2018), and gastrointestinal symptoms (Zhang, Bansal, Go, & Hsu, 2015) are among the most common co-occurring symptoms in CKD (Lockwood et al, 2019). Although variable center approaches are useful in examining relationships among homogeneous populations (Conley, 2017), variable-centered approaches to clustering symptoms are complicated by difficulty interpreting symptom clusters due to heterogeneity of symptom response patterns, thereby limiting their clinical utility (Conley, 2017;Lockwood et al, 2019;Ryan et al, 2019).…”
mentioning
confidence: 99%
“…A review reported that patients on dialysis experienced 6–20 symptoms (Almutary et al., 2013). In addition, several studies found that these symptoms co‐occurred in specific patterns and formed clusters (Cao, Tian, & Lin, 2017; Lockwood et al., 2018). A symptom cluster can be defined as a group of two or more symptoms that occur together and share inter‐relationships (Kim, McGuire, Tulman, & Barsevick, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Western Journal of Nursing Research 41(7) synthesize the data while considering the clinical implications of the findings, especially when using person-centered analyses. Lockwood et al (2019) conducted a systematic review of symptom clusters in patients with CKD. Results indicated that the number of clusters varied from two to five across studies, there were similarities in clusters across studies, and individual symptoms comprising a cluster varied widely.…”
mentioning
confidence: 99%
“…In this issue of the Western Journal of Nursing Research , Ryan et al (2019) and Lockwood et al (2019) help to propel the science of symptom clusters forward through different approaches: one a multimethod statistical analysis of symptom clusters in patients with acute coronary syndrome (ACS) and the other a systematic review of symptom clusters in individuals with chronic kidney disease (CKD). Ryan et al (2019) confirmed that there were few, yet critical, differences in how symptoms clustered using both variable-centered and person-centered methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation